Influence of Structural Decisions Strategy on Organizational Performance of Cement Manufacturing Firms in Kenya - Karuga, Charles; Wairimu, Kibe; Yatich, Henry (International Journal of Strategic Management, 2023)
Purpose: The study examined the influence of structural decisions strategy on organizational performance of cement manufacturing firms in Kenya. Methodology: This research employed the positivism philosophy and concurrent triangulation research design. The research was conducted in the Kenyan cement industry. The eight cement production companies made up the target population of the research and are located in the counties of Kisumu, Nairobi, Mombasa, Machakos, Nakuru, and Kajiado were the subject of the study. Whereas, the units of observation of the research comprised of all employees in the 7 cement firms. The research, further, used the census method and the stratified random sampling technique to select a sample size of 365 employees included 37 managers, 322 non-managers and 6 CEOs distributed per company. The study data was then gathered using a questionnaire and interview schedule for main data collection and a secondary data collection sheet for secondary data collection. Findings: The findings of the research revealed that structural decision strategy is one of the operational strategies that is employed by the cement manufacturing firms to influence their organizational performance. This was according to the high level of agreement by most of the respondents noted in the descriptive results. The study also found that structural decision strategies had a positive and significant relationship with organizational performance of cement manufacturing firms in Kenya. The regression results also led to the rejection of the null hypothesis, thus adopting the alternative hypothesis; structural decision strategy has a significant influence on organizational performance of cement manufacturing firms in Kenya. Unique Contribution to Theory, Practice and Policy: The theories were relevant to this study as they emphasized on the need to identify both the dysfunctions and functional effects of particular structural arrangements on organizational performance of cement firms. Thus, the theories will also be applicable to other studies with such related research topics. The management of cement firms should effectively take part in the decentralization of management structures and specialization of departments in order to improve managerial efficiency and employee performance. Policymakers should establish operating policies and procedures that are supportive of the firms' set objectives and goals.